A survey on graduates' curriculum-based knowledge gaps in software testing - Scatalon, Lilian P.; Fioravanti, Maria Lydia; Prates, Jorge M.; Garcia, Rogerio E. [UNESP]; Barbosa, Ellen F. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
This research full paper presents a study on graduates' knowledge gaps in software testing according to industry needs. Several studies indicate that students graduate from computing programs with a knowledge gap in software testing. In this sense, we aimed to investigate in details this broader testing gap, by considering gaps in the level of testing topics. We conducted a survey with Brazilian practitioners in order to collect data (N=90). For each testing topic, knowledge gaps were calculated as the difference between what respondents' learned/practiced in undergraduate courses and what they actually applied in industry after graduating. Results provide evidence on points that could be improved in software testing education. Firstly, for all testing topics there was a negative gap on practice activities. This means that students could benefit from more testing assignments throughout the curriculum. Regarding gaps in concepts, some testing topics presented negative gaps (such as test in web applications) and others positive (such as test in aspect oriented software and mutation analysis). Therefore, results suggest that it is possible to counterbalance them in order to reduce the existing gaps. We also present respondents' opinions about their experience in software testing education and industry practices.